PM.11 A Label-Free SRM Workflow Identifies a Subset of Pregnancy Specific Glycoproteins as Novel Predictive Markers of Early-Onset Pre-Eclampsia. (26th April 2013) - Blankley, RT; Fisher, C; Westwood, M; North, RA; Philip, Baker; Walker, M; Whetton, T; McCowan, L; Dekker, G; Unwin, R; Myers, JE
Abstract : Objective: The aim of this study was to identify and verify plasma protein markers which may add to predictive algorithms for pre-eclampsia (PE) in asymptomatic nulliparous women. Methods: We used a quantitative mass spectrometry (MS) approach to identify proteins with abundance changes in plasma (15 weeks) taken from women who subsequently develop PE recruited to the international SCOPE study. We developed a novel, targeted, label-free MS method, selective reaction monitoring (SRM) which enabled robust and reproducible verification of these proteins in a further 100 samples (16 early-onset PE, 42 late-onset PE, 42 controls). Results: We identified and quantified >500 plasma proteins, and prioritised a set of candidate predictive markers. The two most promising, Platelet Basic Protein (PBP/NAP-2) and Pregnancy-specific glycoprotein (PSG)-9 were selected for further verification. The SRM method was validated extensively using dilution experiments for PSG proteins and by comparison to a commercial ELISA for NAP-2. NAP-2 was only elevated in a subset of women with PE, however, peptides unique to PSG-9 and PSG-5 were consistently elevated in women with subsequent early onset PE (p < 0.01; AUCs 0.72–0.75). Other PSG peptides were not different between groups. Conclusion: This study has identified specific PSG proteins as being predictive of early-onset PE. Importantly, use of a highly specific MS method has enabled measurement of individual PSG family members which has not been possible using antibody-based techniques. Future work is needed to determine whether these proteins will improve current prediction algorithms for the identification of PE in low risk nulliparous women.